Optimizing Differentiated Learning for Independence and Critical Thinking in Fifth Grade Student - Nurlaela Nurlaela; Purnama Ningsih; Supriyatman Supriyatman (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study aims to determine the effect of implementing differentiated learning based on learning styles on the improvement of student learning independence and critical thinking skills in science subjects, specifically on the topic of light, in grade V at SD Inpres 1 Inti Bantaya. This research is a quantitative study using a quasi-experimental method conducted on the entire population of grade V students at SD Inpres 1 Inti Bantaya for the 2023/2024 academic year, consisting of two classes with a total of 56 students. The results show that the application of differentiated learning based on learning styles has a positive impact on enhancing students' learning independence. This is evidenced by higher scores in the experimental class compared to the control class across five aspects of learning independence: initiative, self-confidence, responsibility, problem-solving, and self-control. Additionally, the results of the independent t-test indicate a significant difference between the average pretest and posttest scores of students' critical thinking skills in the experimental and control classes. The significance values for the pretest and posttest are 0.000 and 0.009, respectively, indicating that the use of differentiated learning based on learning styles can improve students' critical thinking skills. Based on these findings, it can be concluded that differentiated learning based on learning styles is effective in enhancing learning independence and critical thinking skills among students on the topic of light in grade V at SD Inpres 1 Inti Bantaya.